Secondary Science Education Library Resources for New England's Teacher Education Programs - Lloyd H. Barrow (Journal of Research in Rural Education, 1988)
This paper describes the results of a survey of libraries serving pre-service and graduate level teacher education programs in New England relative to their general education, and science education holdings. In general, serious deficiencies are found to exist at both pre-service and graduate student programs. The patterns of holdings are described and suggestions and implications for educators and librarians are presented.